The nurse’s role in preventing infections in the operating theatre - Książek, Janina; Piotrkowska, Renata; Tatur, Grażyna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2008)
In order to lower the risk of infecting surgical wounds it is necessary to obey the rules for infection control in the operating theatre. It should be remembered that surgical wound infections constitute a considerable percentage of all hospital infections and they markedly increase the treatment cost. The aim of the study was to analyze the relation between the length of employment, education and knowledge about preventing hospital infections at the operating suite. In order to achieve the aim the following research problems were stated: 1. What knowledge do operating room nurses have about preventing hospital infections at the operating suite? 2. Does the level of operating room nurses’ knowledge depend on their length of employment and education? The research material comprised 30 operating room nurses with varied length of employment, secondary level of medical education or post-secondary nursing course and a qualifying course, which all the respondents had. The method of a diagnostic survey and a statistical method were used in the study. For calculations Student’s t-test was used. The obtained results indicated that neither the type of education nor the length of employment greatly influences the nurses’ knowledge concerning preventing infections at the operating suite. Although the survey showed that the respondents had deep knowledge on preventing hospital infections at the operating suite, it cannot be stated that all nurses are prepared to play the leading role in preventing infections. This is due to the fact that on the basis of just one operating suite and the nurses working there it cannot be generalized that the knowledge of all nurses is extensive enough for them to be leaders in this area.